Semiotic alteration in translation. Othering, stereotyping and hybridization in contemporary translations from Arabic into Spanish and Catalan - Carbonell i Cortés, Ovidi (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
It is already widely recognized that ‘foreignization’ is a cover word which stands for many different processes of cultural translation, from a problematic literalism which tends to exoticism, to a welcome but rarely achieved ‘othering’ understood as an ethical act of respect for the other ’s specificity. Seen from a pragmatic perspective, what still needs to be assessed are the reasons behind a hypothetic threshold of acceptability and the extent of the unstable and risky space where source culture expectations are challenged as a result of the translator ’s management of socio-cultural biases. Starting from the assumption that cultural translation implies a metonymical move by which key textual elements stand as symbols representing the foreign culture, the proposed article will present a scheme of the pragmatic and semiotic processes at work in translations from Arabic into Spanish and Catalan. A review of recent Spanish translations of contemporary Arabic fiction and the muchacclaimed Catalan translation of the Qur ’an will try to show that instances of hybridization and ambivalent readings occur foremost when semiotic categories are altered as a result of the familiarization of unexpected cultural referents. However, semiotic alteration only happens in the narrow margin allowed by the threshold of acceptability, which is the site of ambivalence.